Evaluation method for deformation of zirconia calcined body due to firing

By coloring the calcined body of zirconium oxide and measuring the color difference, the problem of cumbersome sintering deformation process in the prior art is solved, and the effect of efficient evaluation and improvement of production efficiency is achieved.

JP7658874B2Active Publication Date: 2025-04-08KURARAY NORITAKE DENTAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021162046
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-04-08
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

The prior art requires cutting and sintering samples when evaluating the deformation problems caused by zirconia during sintering, resulting in cumbersome processes and low production efficiency.

Method used

The degree of deformation during sintering was evaluated by coloring the calcined body and measuring the color difference between the layers.

Benefits of technology

It is possible to efficiently evaluate the degree of sintering deformation without cutting or sintering the calcined body of zirconium oxide, which improves production efficiency and reduces material waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658874000001
    Figure 0007658874000001
  • Figure 0007658874000002
    Figure 0007658874000002
  • Figure 0007658874000003
    Figure 0007658874000003
Patent Text Reader

Abstract

To provide a method capable of simply evaluating presence / absence of deformation due to calcination without cutting or calcining a calcined zirconia.SOLUTION: A method for evaluating deformation of a calcined zirconia due to calcination comprises: a coloring step of coloring a calcined zirconia having at least two layers, with a colorant; and a step of evaluating color differences of the respective layers of the calcined zirconia colored in the coloring step. According to one embodiment, the calcined zirconia is preferably a zirconia blank. According to another embodiment, the calcined zirconia is preferably a processed body having a shape of a dental prosthesis. Further, according to another embodiment, the at least two layers preferably have different BET specific surface areas.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating deformation due to firing of a calcined zirconia body. [Background technology]

[0002] Traditionally, metals have been widely used as dental products (for example, dental prostheses such as typical veneers and dental implants, orthodontic products, and dental implant products). However, metals have the drawback of being clearly different in color from natural teeth and lacking in aesthetics, and metal elution can cause allergies. Therefore, in order to solve the problems associated with the use of metals, ceramic materials such as aluminum oxide (alumina) and zirconium oxide (zirconia) have begun to be used in dental products as alternative materials to metals. In particular, zirconia is strong and relatively aesthetically pleasing, and demand for it is increasing, especially in conjunction with the recent drop in prices.

[0003] To manufacture dental products using zirconia, the shape of the dental prosthesis is cut out using a CAD / CAM device from a workpiece, which is a zirconia calcined body semi-sintered at a temperature 400°C to 700°C lower than the temperature at which an ideal sintered body is obtained, and the cut-out zirconia workpiece is anchored and sintered at a maximum firing temperature of 1400°C to 1650°C. The workpiece, which is a zirconia calcined body, has a shape such as a disk and is called a zirconia blank. In order to make dental prostheses closer to the appearance of natural teeth, zirconia blanks with a multilayer structure in which multiple layers are stacked have also been developed.

[0004] Currently, zirconia blanks with a multilayer structure distributed in the dental industry have different compositions for each layer. When zirconia is fired to form a sintered body, each layer shrinks due to firing. Here, due to the difference in composition of each layer among the multiple layers, the shrinkage rate of each layer during firing (hereinafter also referred to as "firing shrinkage rate") may differ. For example, the firing shrinkage rate of the layer corresponding to the enamel layer in the zirconia blank may differ from that of the body layer corresponding to the gum area of ​​the tooth. When the firing shrinkage rate of each layer is significantly different, deformation or cracking occurs during firing, and due to uneven and complex deformation, the compatibility of dental products with teeth is greatly affected, which has become a problem. In addition, since the zirconia blank has a white appearance, it is difficult to distinguish each layer, and it is difficult to judge by visual inspection whether there is a difference in the shrinkage rate of each layer. Therefore, a method for evaluating the deformation due to firing has been required. For example, the methods disclosed in Patent Documents 1 and 2 have been proposed as methods for evaluating the deformation due to firing.

[0005] Patent Document 1 describes a method for evaluating deformation due to sintering of a zirconia blank having a multilayer structure in which each layer has a different amount of yttria.

[0006] Patent Document 2 describes a method for evaluating the deformation caused by sintering of a zirconia blank having a multilayer structure. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-163246 A [Patent Document 2] JP 2020-75858 A Summary of the Invention [Problem to be solved by the invention]

[0008] The inventors have studied the evaluation method of Patent Document 1, and found that it is necessary to cut a six-piece bridge from a zirconia blank, which is a calcined body, and then sinter it, and both steps are performed for each sample, which is a problem of considerable labor. In particular, in the case of a long-span bridge, which is a shape in which four or more teeth are connected, the volume cut out by cutting is large, and if it is deformed by sintering, the loss of the blank is large, and in addition to being labor-intensive, the method of Patent Document 1 uses a large volume to evaluate the deformation due to sintering, and productivity is also significantly reduced. In addition, in the evaluation method of Patent Document 2, a rectangular parallelepiped sample must be cut out from the zirconia blank and sintered at 1500°C for two hours. Therefore, as in Patent Document 1, the processing and sintering steps take time, and since a part of the zirconia blank is used for evaluation, the number of dental prostheses that can be processed from the zirconia blank is reduced, which is a problem of low productivity.

[0009] An object of the present invention is to provide a method for easily evaluating the degree of deformation caused by sintering, without cutting or sintering a zirconia calcined body. [Means for solving the problem]

[0010] Means for Solving the Problems The present inventors focused on the fact that differences in the degree of coloration of a zirconia calcined body result in differences in the degree of deformation during firing, and as a result of extensive research, found that the problems can be solved by coloring a zirconia calcined body and evaluating the color difference of the zirconia calcined body. Based on this finding, the inventors conducted further research and completed the present invention.

[0011] That is, the present invention includes the following inventions. [1] A coloring step of coloring a zirconia calcined body having at least two layers with a colorant; and evaluating the color difference of each layer of the zirconia calcined body colored in the coloring step. A method for evaluating deformation of calcined zirconia bodies due to firing. [2] The method for evaluating deformation due to sintering of a zirconia calcined body according to [1], wherein the zirconia calcined body is a zirconia blank. [3] The method for evaluating deformation due to firing of a zirconia calcined body according to [1], wherein the zirconia calcined body is a processed body having the shape of a dental prosthesis. [4] The method for evaluating deformation due to firing of a zirconia calcined body according to any one of [1] to [3], wherein the coloring step of coloring the zirconia calcined body with a colorant is carried out by immersing the body in a coloring solution or applying the coloring solution. [5] A method for producing a dental prosthesis, comprising the steps of processing a zirconia blank evaluated by the evaluation method described in [2] to produce a dental prosthesis. [6] A method for producing a dental prosthesis, comprising a step of firing a calcined zirconia body or a processed body thereof evaluated by the evaluation method according to any one of [1] to [4]. Effect of the Invention

[0012] According to the present invention, the degree of deformation due to firing of a zirconia blank can be easily evaluated without cutting and firing the zirconia calcined body. In particular, when manufacturing a dental product having a shape in which multiple prostheses such as implants and long-span bridges, which require a particularly high degree of compatibility when mounted in the oral cavity, are connected, the deformation due to firing can be evaluated without cutting and firing, which is excellent in industrial productivity and industrially advantageous. In addition, according to the present invention, multiple types of blanks held by a dental laboratory or the like can be appropriately (effectively) allocated according to the shape of the prosthesis to be processed (single crown, long-span bridge, etc.). Therefore, the loss of blanks that are cut but cannot be used due to deformation during firing can be significantly improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The method for evaluating deformation due to firing of a zirconia calcined body of the present invention includes a coloring step of coloring a zirconia calcined body having at least two layers with a coloring agent, and a step of evaluating the color difference of each layer of the zirconia calcined body colored in the above step. The evaluation method of the present invention evaluates a zirconia calcined body having a multilayer structure having at least two layers. The term "at least two layers" refers to a layer having two or more regions with different compositions, and includes layers having different properties due to the difference in composition, and a transition portion between layers (between two regions with different compositions) in which the compositions of the layers (two regions with different compositions) are mixed may be present. The number of layers of the zirconia calcined body is not particularly limited as long as it is two or more layers, and may be three, four, five, six, or seven or more layers.

[0014] "Firing" for the evaluation of the variations means firing with a maximum firing temperature falling within the range of 1400°C to 1650°C.

[0015] The zirconia calcined body may be a processed body processed into the shape of a dental product (e.g., a dental prosthesis, etc.), or may be a blank before processing. The zirconia calcined body means a zirconia calcined body having zirconia (ZrO2: zirconium oxide) as the main component, in which zirconia particles (powder) are formed into a block in a state where they are not completely sintered. The main component may be 50% by mass or more. The content of zirconia in the zirconia calcined body according to the present invention is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. The density of the zirconia calcined body is 2.7 g / cm 3 The density of the calcined zirconia body is preferably 4.0 g / cm 3 Less than 3.8 g / cm is preferred. 3 Less than 3.6 g / cm is more preferable. 3 The following is even more preferable. When the density is within this range, forming can be easily performed. The density of the calcined body can be calculated, for example, by dividing the mass of the calcined body by the volume of the calcined body.

[0016] The three-point bending strength of the zirconia calcined body is preferably 15 to 70 MPa, more preferably 18 to 60 MPa, and even more preferably 20 to 50 MPa. The bending strength can be measured using a test piece having a thickness of 5 mm, a width of 10 mm, and a length of 50 mm, in accordance with ISO 6872:2015, except for the size of the test piece. The surface and C surface of the test piece (the surface where the corner of the test piece is chamfered at an angle of 45°) are surface-finished in the longitudinal direction with sandpaper of No. 600. The test piece is arranged so that the widest surface faces vertically (load direction). In the bending test measurement, the span is 30 mm, and the crosshead speed is 0.5 mm / min.

[0017] A preferred embodiment of the present invention is a method for evaluating deformation of a zirconia calcined body caused by firing, in which the zirconia calcined body is a zirconia blank. The shape of the zirconia blank may be a disk shape or a block shape. The term "blank" refers to a solid block of a material that can be cut, carved, or machined to obtain the shape of a dental product (e.g., a dental prosthesis). In other words, the term "blank" refers to a workpiece having a predetermined shape (e.g., a disk shape, a block shape) before being machined into the shape of a desired dental product.

[0018] By evaluating zirconia blanks, zirconia blanks that are significantly deformed after processing into the shape of a dental product (e.g., a dental prosthesis) and sintering before being obtained by cutting and sintering and that cannot be used can be discarded before processing, thereby reducing unnecessary processing and sintering. In addition, in dental laboratories, etc., those that are less deformed by sintering can be allocated to long-span bridges, and those that are more deformed by sintering can be allocated to single crowns. In addition, since it is possible to detect zirconia blanks that are deformed by sintering, the yield in the manufacture of zirconia blanks can be improved, which is industrially advantageous.

[0019] In the zirconia calcined body having at least two layers, the at least two layers may contain a stabilizer (hereinafter also referred to as "stabilizer") capable of suppressing the phase transition of the zirconia powder. In one embodiment, the at least two layers have a different stabilizer content. The difference in the stabilizer content between the layers may be 0.1 mol% or more with respect to the total molar number of zirconia and the stabilizer. In another embodiment, the at least two layers have different types of stabilizers. In yet another embodiment, the types and contents of the stabilizers are different. In another embodiment, the at least two layers may have different total light transmittances of the sintered body after firing. The difference in the total light transmittances of the sintered body after firing may be 0.1% or more between the layers of the sintered body after firing. The total light transmittance of each layer of the sintered body after firing is not particularly limited, and may be 15% or more and 60% or less, 18% or more and 55% or less, or 20% or more and 50% or less. The total light transmittance is a value measured using a D65 light source in accordance with JIS K 7361-1:1997 for a sample of 1.0 mm thick sintered body. The total light transmittance can be measured by preparing a sample of 1 mm thick and using a known measuring device (for example, a turbidimeter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.)). In another embodiment, at least two layers may have different total light transmittances at a wavelength of 600 nm in a sample of 1.0 mm thick sintered body after firing (hereinafter, also referred to as "total light transmittance at a wavelength of 600 nm"). The difference in total light transmittance at a wavelength of 600 nm between layers of the sintered body after firing may be 0.1% or more. The total light transmittance at a wavelength of 600 nm in each layer of the sintered body after firing is not particularly limited, and may be 15% or more and 60% or less, 18% or more and 55% or less, or 20% or more and 50% or less. The total light transmittance at a wavelength of 600 nm can be measured using a known spectrophotometer (for example, the trade name "UV-3600i Plus UV-Visible Spectrophotometer" manufactured by Shimadzu Corporation) using a sample of the sintered body having a thickness of 1.0 mm. In another embodiment, the at least two layers have a monoclinic ratio f mThe ratio of monoclinic crystals in zirconia f may be different. m The difference is calculated by the formula (2) described later. m The difference may be 1% or more.

[0020] Examples of the stabilizer include calcium oxide (CaO), magnesium oxide (MgO), yttria (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), niobium oxide (Nb2O5), lanthanum oxide (La2O3), erbium oxide (Er2O3), and praseodymium oxide (Pr6O 11 Examples of the stabilizer include oxides such as samarium oxide (Sm2O3), europium oxide (Eu2O3) and thulium oxide (Tm2O3). The stabilizer may be used alone or in combination of two or more. The content of the stabilizer in the zirconia calcined body of the present invention can be measured, for example, by inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis, etc. In the zirconia calcined body of the present invention, the content of the stabilizer is preferably 0.1 to 18 mol%, more preferably 1 to 15 mol%, and even more preferably 2 to 8 mol%, based on the total moles of zirconia and the stabilizer.

[0021] In an embodiment, from the viewpoint of mechanical strength and translucency of the dental prosthesis, which is the zirconia sintered body finally obtained, the zirconia calcined body preferably contains yttria as a stabilizer. The content of yttria is preferably 3.0 mol% or more, more preferably 3.5 mol% or more, even more preferably 3.8 mol% or more, and particularly preferably 4.0 mol% or more, based on the total molar number of zirconia and yttria. When the content of yttria is 3.0 mol% or more, the translucency of the zirconia sintered body can be increased. In addition, the content of yttria is preferably 7.5 mol% or less, more preferably 7.0 mol% or less, even more preferably 6.5 mol% or less, and particularly preferably 6.0 mol% or less, based on the total molar number of zirconia and yttria. When the content of yttria is 7.5 mol% or less, the decrease in mechanical strength of the dental prosthesis, which is the zirconia sintered body finally obtained, can be suppressed. The yttria content of each layer in the zirconia calcined body can be appropriately adjusted within the above range so that the content between layers differs and each layer corresponds to an assumed layer of a natural tooth (enamel, dentin, dental pulp, etc.).

[0022] The object (blank, etc.) evaluated by the method of the present invention may have at least two layers with different or the same BET specific surface areas. When the BET specific surface areas are different, the degree of impregnation of the colorant into the blank, etc. differs due to the difference in the BET specific surface areas, resulting in a color difference after coloring. When the BET specific surface areas are the same, the degree of impregnation of the colorant into the blank, etc. is the same due to the same BET specific surface areas, and no color difference occurs after coloring. As the difference in the BET specific surface areas increases, the color difference also increases, making it possible to predict the degree of deformation. The BET specific surface area can be measured in accordance with JIS Z 8830:2013.

[0023] The zirconia calcined body of the present invention may contain additives as necessary. Examples of additives include binders, colorants (including pigments and composite pigments), fluorescent agents, alumina (Al2O3), titanium oxide (TiO2), silica (SiO2), and the like. The additives may be used alone or in combination of two or more. The object (blank, etc.) evaluated by the method of the present invention may have at least two layers containing different types of additives, or may have different additive contents.

[0024] Examples of the binder include polyvinyl alcohol, methyl cellulose, carboxymethyl cellulose, acrylic binders, wax-based binders (paraffin wax, etc.), polyvinyl butyral, polymethyl methacrylate, ethyl cellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, polystyrene, atactic polypropylene, methacrylic resin, and stearic acid.

[0025] Examples of the pigment include oxides of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb and Er (specifically, NiO, Cr2O3, etc.), and oxides of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd and Tb are preferred, and oxides of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd and Tb are more preferred. In addition, the zirconia calcined body of the present invention may not contain erbium oxide (Er2O3). Examples of the composite pigment include composite oxides such as (Zr,V)O2, Fe(Fe,Cr)2O4, (Ni,Co,Fe)(Fe,Cr)2O4·ZrSiO4, (Co,Zn)Al2O4, etc. Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y,Gd,Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, BaMgAl 10 O17 :Eu, etc.

[0026] The method for producing the zirconia calcined body is not particularly limited, and a known method can be used. As a method for producing the zirconia calcined body, for example, the method described in International Publication No. 2021 / 100876 can be used. Specific examples of the method for producing the zirconia calcined body include a manufacturing method including a molding step of molding a zirconia composition into a molded body, and a step (calcination step) of firing (i.e., calcining) the molded body produced in the molding step at a temperature at which the zirconia particles do not sinter.

[0027] The zirconia composition used in the molding step may, for example, contain zirconia powder and, if necessary, may further contain a stabilizer capable of suppressing the phase transition of the zirconia powder. In a preferred embodiment, the zirconia composition contains zirconia powder and a stabilizer capable of suppressing the phase transition of the zirconia powder.

[0028] In one embodiment, in the zirconia composition containing the stabilizer used in the molding step, at least a part of the stabilizer may not be solid-dissolved in zirconia. The fact that a part of the stabilizer is not solid-dissolved in zirconia can be confirmed, for example, by an X-ray diffraction (XRD) pattern. When a peak derived from the stabilizer is confirmed in the XRD pattern of the zirconia composition, it means that the stabilizer is present in the zirconia composition and is not solid-dissolved in zirconia. When the entire amount of the stabilizer is solid-dissolved, basically, a peak derived from the stabilizer is not confirmed in the XRD pattern. However, depending on conditions such as the crystal state of the stabilizer, even if there is no peak of the stabilizer in the XRD pattern, the stabilizer may not be solid-dissolved in zirconia. When the main crystal system of zirconia is a tetragonal system and / or a cubic system and there is no peak of the stabilizer in the XRD pattern, it is considered that most (basically all) of the stabilizer is solid-dissolved in zirconia.

[0029] In the zirconia composition containing the stabilizer, when the stabilizer is yttria, the abundance rate f of yttria that is not dissolved in zirconia (hereinafter referred to as "undissolved yttria") in the zirconia composition is y can be calculated based on the following formula (1).

[0030]

number

[0031] In another embodiment of the zirconia composition containing the stabilizer, the stabilizer is yttria, the abundance ratio of undissolved yttria f y is preferably greater than 0%, more preferably 1% or more, even more preferably 2% or more, and even more preferably 3% or more. y The preferred upper limit of f depends on the content of yttria in the zirconia composition. When the content of yttria is 7.5 mol% or less based on the total molar number of zirconia and yttria, the same translucency as that obtained by normal firing can be obtained in a short time. y For example, when the content of yttria is 3.0 mol% or more and 4.5 mol% or less with respect to the total mole number of zirconia and yttria, f y When the content of yttria is more than 4.5 mol% and not more than 6 mol% based on the total mole number of zirconia and yttria, f yWhen the content of yttria is more than 6 mol% and not more than 7.5 mol% based on the total mole number of zirconia and yttria, f y may be no more than 11%.

[0032] In another embodiment, in the zirconia composition containing the stabilizer, the main crystal system of the zirconia is preferably a monoclinic system. The term "main crystal system is a monoclinic system" refers to the proportion of the monoclinic system in the zirconia calculated by the following formula (2) based on the XRD peak by CuKα radiation, relative to the total amount of all crystal systems (monoclinic system, tetragonal system, and cubic system) in the zirconia. m The meaning of each symbol in the formula (2) is the same as that in the formula (1). In the zirconia composition of the present invention, the proportion of monoclinic crystals in the zirconia, f m is preferably 55% or more, more preferably 60% or more, even more preferably 70% or more, even more preferably 80% or more, particularly preferably 90% or more, and most preferably 95% or more. The main crystal system in the zirconia composition can contribute to increasing the changeover temperature and shortening the firing time.

[0033]

number

[0034] The method for producing the zirconia composition is not particularly limited, and a known method can be used. As the method for producing the zirconia composition, for example, the method described in International Publication No. 2019 / 026811 and the method described in International Publication No. 2021 / 100876 can be used. Specific examples of the method for producing the zirconia composition include a method including a step of mixing a zirconia powder and a stabilizer in a predetermined ratio to prepare a mixture (mixing step), and pulverizing the mixture until the desired average particle size of the zirconia particles is obtained, and further until the desired BET specific surface area of ​​the zirconia powder is obtained as necessary. After the mixing step and / or the pulverizing step, the zirconia composition can be dried by spray drying using a spray dryer or the like to form the zirconia composition into a granular form (drying step).

[0035] The average particle size of the zirconia particles after the pulverization process is preferably in the range of 0.06 μm to 0.45 μm. The average particle size can be measured by a laser diffraction / scattering type particle size distribution measurement method. Specifically, the average particle size can be measured on a volume basis using a laser diffraction type particle size distribution measurement device (SALD-2300: manufactured by Shimadzu Corporation) and a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.

[0036] The BET specific surface area of ​​the zirconia powder after the grinding process is 6.5 m when measured in accordance with JIS Z 8830:2013. 2 / g or more, and 6.8m 2 More preferably, it is 7.0m 2 More preferably, it is 6.5m / g or more. 2 / g or more, the sintered body can be prevented from becoming cloudy after firing. 2 / g or less, and 2 / g or less is more preferable, and 20m 2 / g or less is more preferable. 2 / g or less, the material is less susceptible to temperature variations in the firing furnace.

[0037] The molding method of the zirconia composition may be, for example, a molding method such as press molding, injection molding, or stereolithography. In addition, multi-stage molding may be performed. For example, the zirconia composition may be press molded and then further subjected to CIP treatment. The above-mentioned additives such as binders and colorants may be appropriately added in each step.

[0038] In the calcination step, the molded body obtained as described above is sintered at a temperature at which the zirconia particles do not sinter. For example, the calcination temperature (calcination temperature) is preferably 700°C or higher, more preferably 800°C or higher. The calcination temperature is preferably 1200°C or lower, more preferably 1100°C or lower, even more preferably 1000°C or lower, even more preferably 980°C or lower, and particularly preferably 950°C or lower. The calcination can be performed in air. It is considered that the calcination step can dissolve a part of the stabilizer in zirconia, facilitate the dissolution of the stabilizer in the subsequent sintering step, and improve the properties of the zirconia sintered body. In one embodiment, the calcination conditions in the calcination step are preferably such that the main crystal system of zirconia when cooled after calcination is not a tetragonal system or a cubic system as described above. In another embodiment, the calcination conditions in the calcination step are preferably such that at least a part of the stabilizer is not dissolved in zirconia.

[0039] Another preferred embodiment is a method for evaluating deformation due to firing of a zirconia calcined body, in which the zirconia calcined body is a processed body having the shape of a dental prosthesis. The processed body having the shape of a dental prosthesis can be produced by cutting a zirconia blank, which is a zirconia calcined body. The processed body having the shape of a dental prosthesis can be produced, for example, by using a commercially available CAD / CAM system. Examples of dental prostheses include crowns and long span bridges. Since the evaluation method of the present invention can evaluate deformation due to firing regardless of whether cutting is performed or not, a zirconia sintered body processed into the shape of a dental product (for example, a dental prosthesis) can also be used as the evaluation object before obtaining the zirconia sintered body by firing. By using a zirconia calcined body processed into the shape of a dental prosthesis as the evaluation object, a zirconia calcined body that is significantly deformed after firing and cannot be used can be discarded before firing, which reduces unnecessary firing and is industrially advantageous.

[0040] The coloring step of coloring the zirconia calcined body with a colorant is carried out by immersing the zirconia calcined body in a coloring solution or by applying the coloring solution to the zirconia calcined body.

[0041] The colorant that colors the zirconia calcined body may be a colorant that is decolorized by firing the zirconia calcined body, or a colorant that is not decolorized by firing. The "decolorization" of a colorant that is decolorized by firing refers to the color difference ΔE between the zirconia calcined body before coloring and the zirconia calcined body after firing when the colorant and the zirconia calcined body are fired at 700°C or higher. * ab is calculated and is approximately 0 (preferably less than 0.50). * The method for measuring ab is as described in the Examples below. In an embodiment in which the zirconia calcined body is a processed body having the shape of a dental prosthesis, a colorant that is decolorized by firing is preferably used as the colorant.

[0042] As colorants that are decolorized by baking, food colorants are preferred from the viewpoint of safety for the human body, and more preferably have a boiling point of 400° C. or lower. Specific examples of such food dyes include organic dyes containing two or more aromatic groups, having a ketimide group or an azo group as a chromophore, and a sulfone group as an auxochrome, such as Yellow No. 4 (tartrazine), Yellow No. 5 (Sunset Yellow FCF), Red No. 2 (amaranth), Red No. 102 (New Coccine), Blue No. 1 (Brilliant Blue FCF), Blue No. 2 (indigo carmine), Green No. 3 (Fast Green FCF), and Red No. 102 (New Coccine); organic dyes containing a condensed aromatic group with a xanthene nucleus (xanthene dyes), such as Acid Red 289, Bromopyrogallol Red, Rhodamine B, Rhodamine 6G, Rhodamine 6GP, Rhodamine 3GO, Rhodamine 123, Eosin, Eosin B, Eosin Y, Fluorescein, and Fluorescein Isothiocyanate; and cochineal dyes (carminic acid dyes). The colorant that is decolorized by baking can be used alone or in appropriate combination of two or more kinds.

[0043] As the coloring agent that does not discolor by firing, a known coloring agent used for coloring dental ceramic materials can be used, and a commercially available product can be used. For example, Luxen Zirconia Color Liquid (manufactured by Geomedi Co., Ltd.) can be used. When using a coloring agent that does not discolor by firing, for example, the coloring agent is impregnated only on the very surface of the evaluation object (disk, etc.) so that the coloring agent does not penetrate into the inside of the evaluation object (disk, etc.), and the evaluation object (disk, etc.) can be used to prepare a prosthesis without being affected by the coloring agent even after the coloring evaluation.

[0044] The method of immersing the zirconia calcined body in the coloring solution and the method of applying the coloring solution to the zirconia calcined body are not particularly limited, and any known method can be used. In these methods, the concentration of the coloring solution, the immersion time, the application method, etc. are not limited as long as the zirconia calcined body can be colored to a desired color.

[0045] The color tone of the colored zirconia calcined body to be evaluated (hereinafter, also referred to as "colored zirconia calcined body") obtained by the coloring step of coloring the zirconia calcined body with a coloring agent is not particularly limited. However, in order to easily evaluate the degree of deformation due to firing from the color difference, it is preferable to use L * a * b * Color system (JIS Z 8781-4:2013 Color measurement-Part 4: CIE 1976 L * a * b * Color space) * is preferably 40.0 to 99.0, more preferably 55.0 to 95.0, and further preferably 70.0 to 93.0. * is preferably -50.0 to 70.0, more preferably -30.0 to 50.0, and further preferably -10.0 to 30.0. * is preferably -40.0 to 60.0, more preferably -20.0 to 40.0, and further preferably -15.0 to 35.0. * a * b * The method for measuring the color tone according to the color system is as described in the Examples below. * a * b * The color tone can be measured by a known method and device according to the color system.

[0046] The step of evaluating the color difference of each layer of a colored zirconia calcined body (preferably a colored zirconia blank) (hereinafter also referred to as the "color difference evaluation step") can also be performed by visually judging the color difference. The greater the color difference of each layer of the colored zirconia calcined body, the lower the compatibility with a dental arch model or the compatibility when worn in the oral cavity, making it impractical as a prosthesis. One embodiment is a method (X-1) for evaluating deformation due to firing of a zirconia calcined body, in which the color difference evaluation step is performed by visually judging the color difference of each layer.

[0047] As another embodiment (X-2), the color difference ΔE of each layer of a colored zirconia calcined body (preferably, a colored zirconia blank)* An example of an evaluation method is to measure the color difference ΔE ab using a color difference measuring device such as a spectrophotometer (product name "Crystal Eye"). The measurement method using a spectrophotometer is as described in the examples below. * The larger ab is, the lower the compatibility with the dental model or the compatibility when worn in the oral cavity becomes, and the less practical it becomes as a prosthesis. In addition, as an embodiment (X-2), for example, a method of evaluating the color difference of each layer based on the following evaluation criteria can be mentioned. Color difference ΔE * If ab is 0.7 or less, it can be applied to a long-span bridge that has four or more teeth (e.g., six) in a row; Color difference ΔE * When ab is greater than 0.7 and less than 1.4, it can be applied to three-bridge; Color difference ΔE * If ab is 1.4 or more but less than 2.2, it can be applied to single crowns; Color difference ΔE * If ab is 2.2 or more but less than 4.0, it is difficult to recommend its use even for single crowns; Color difference ΔE * If ab is 4.0 or more, it cannot be applied to long span bridges, three-piece bridges, or single crowns. In addition, the above judgment criteria "color difference ΔE * "ab" means the maximum value of any two layers. In other words, "color difference ΔE * The value is obtained by selecting the combination of two layers that gives the maximum value for "ab" and performing calculations based on those two layers.

[0048] In addition, even when the same colored zirconia calcined body (preferably a colored zirconia blank) is evaluated in embodiment (X-2), the present invention also includes modified examples in which the evaluation criteria for color difference are changed depending on conditions such as the type and amount of colorant used, and the impregnation time. For example, in one embodiment, the evaluation criteria for color difference ΔE * For ab, the upper limit and / or lower limit may be increased or decreased within a range of 0.1 to 5, or may be increased or decreased within a range of 0.5 to 3. The reason why such a modified example can be used is that the color difference ΔE* It was found that the larger ab (the maximum value of any two layers) is, the lower the compatibility with the dental model or the compatibility when worn in the oral cavity tends to be. Therefore, even when the conditions such as the coloring agent and the impregnation time are changed, the color difference ΔE * This is because ab can be relatively evaluated according to the above tendency by measuring the ab. The above modified example can be used as the evaluation method of the present invention to relatively evaluate and select the applicability to a dental model or the suitability when worn in the oral cavity according to the number of sample groups of colored zirconia calcined bodies to be evaluated, etc.

[0049] In the evaluation method of the present invention, the color difference ΔE * By evaluating ab, the degree of deformation due to firing can be determined in the zirconia calcined body before cutting. For example, in applications such as dental prostheses such as long span bridges having four or more (e.g., six) teeth connected together, the volume cut out from the zirconia blank by cutting is large, so that zirconia blanks that will be significantly deformed after firing can be easily detected before cutting and firing, which is industrially advantageous.

[0050] In the prior art, when evaluating deformation due to sintering, it is assumed that a processed body is used, which is sintered and then evaluated (Patent Documents 1 and 2), and there was no idea of ​​evaluating the change after sintering in the state of the zirconia blank, which is the processed body before processing. Therefore, for example, when the zirconia calcined body is a zirconia blank, the color difference of the zirconia blank is the appearance before processing, so it was never thought that the deformation due to sintering can be evaluated by the color difference before cutting processing for the deformation after sintering of the processed body, even though it does not go through two steps of cutting processing of the zirconia blank and sintering the processed body.

[0051] Another embodiment of the present invention is a method for producing a dental prosthesis, which includes a step of processing a zirconia blank evaluated by any one of the above-mentioned evaluation methods to produce a dental prosthesis. The dental prosthesis is not particularly limited, and can be produced using a commercially available CAD / CAM system (e.g., Katana (registered trademark) CAD / CAM system including dental CAD / CAM machines DWX-52D and DWX-52DCi (manufactured by Roland DG Corporation)).

[0052] The maximum firing temperature for firing the zirconia calcined body or its processed body can be from 1400°C to 1650°C. The maximum firing temperature is preferably 1420°C or higher, and more preferably 1450°C or higher. The maximum firing temperature is preferably 1620°C or lower, and more preferably 1600°C or lower. The retention time at the maximum firing temperature is not particularly limited, and may be 10 minutes to 4 hours, 15 minutes to 3 hours, or 30 minutes to 2.5 hours. A known firing furnace can be used for firing. The firing furnace used for firing is an atmospheric furnace, which may be a box furnace, a crucible furnace, a tubular furnace, a hearth lifting furnace, a continuous furnace, or a rotary kiln, or may be a resistance heating furnace, an induction heating furnace, a direct current type electric furnace, an IH furnace, a high frequency furnace, or a microwave furnace, and may be a metal heating element, silicon carbide, molybdenum disilicide, lanthanum chromium yarn, molybdenum, carbon, tungsten, or the like, and may be used as a heating element susceptor using SiC. A firing furnace combining any two or more of these may also be used. As a commercially available dental porcelain firing furnace, for example, Noritake Katana (registered trademark) F-1N (manufactured by SK Medical Electronics Co., Ltd.) or the like may be used. The temperature rise rate and temperature fall rate can be appropriately set according to the use conditions of each firing furnace. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples, and many modifications within the scope of the technical concept of the present invention are possible by those having ordinary skill in the art.

[0054] [Measurement of BET specific surface area of ​​zirconia blank] The BET specific surface area of ​​the calcined zirconia blank was measured by nitrogen adsorption using the BET one-point method (flow method). The calcined zirconia was pulverized to a diameter of about 1 mm to obtain a measurement sample. A gas adsorption type specific surface area measurement device (device name: Macsorb (registered trademark) 1201, manufactured by Mountec Co., Ltd.) was used as the measurement device, and measurements were performed in accordance with JIS Z 8830:2013 (n=1). Prior to the measurement, the powder measurement sample was pretreated by degassing it by heating at 120°C for 5 minutes, and then measured.

[0055] [Coloring of zirconia blanks] [Examples 1 to 7] In Examples 1 to 7, Edible Red No. 102 (manufactured by Kyoritsu Foods Co., Ltd.) was used as the coloring solution. In Example 1, 0.3 mass% of Edible Red No. 102 was added to purified water and mixed with a magnetic stirrer for 30 minutes to prepare a coloring solution. Next, Blank 1 (zirconia blank having a three-layer multilayer structure as described in Table 1 below) was immersed in the coloring solution for 1 second so that the entire blank was immersed, and then dried indoors for 30 minutes to obtain a colored zirconia blank. In Examples 2 to 7, colored zirconia blanks were obtained in the same manner as in Example 1, except that Blank 1 was replaced with Blanks 2 to 7, respectively (zirconia blanks having a multilayer structure as shown in Table 1 below).

[0056] [Color difference measurement] The side of the colored zirconia blank (cross section in the direction of lamination of each layer) was measured using a spectrophotometer (product name "Crystal Eye") manufactured by Olympus Corporation, with a 7-band LED light source and a white background. * a * b * Color system (JIS Z 8781-4:2013 Color measurement-Part 4: CIE 1976 L * a * b * The chromaticity is measured using the color space, and the brightness index L * , color coordinate a * , b * Using the above, the layers of the colored zirconia blank were measured. *a * b * L of each layer in the color system * a * b * After measuring the value, the color difference ΔE between each layer was calculated using the following formula (1). * The ab was calculated, and the results are shown in Table 1. ΔE * ab = {(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 (1) (In the formula, ΔL * is the lightness index between two layers L * represents the difference between * and Δb * are the color coordinates between the two layers, * , b * It represents the difference between (Note that the above criteria for color difference ΔE * "ab" means the maximum value of any two layers. In other words, "color difference ΔE * The value is obtained by selecting the combination of two layers that gives the maximum value for "ab" and calculating based on those two layers.)

[0057] <Evaluation criteria based on color difference for degree of deformation due to firing> Obtained color difference ΔE * Depending on the value of ab, it can be evaluated according to the following criteria. Color difference ΔE * If ab is less than or equal to 0.7, it is applicable to long span bridges; Color difference ΔE * When ab is greater than 0.7 and less than 1.4, it can be applied to three-bridge; Color difference ΔE * If ab is 1.4 or more but less than 2.2, it can be applied to single crowns; Color difference ΔE * If ab is 2.2 or more but less than 4.0, it is difficult to recommend its use even for single crowns; Color difference ΔE * If ab is 4.0 or more, it cannot be applied to long span bridges, three-piece bridges, or single crowns.

[0058] [Checking the degree of deformation due to firing] Next, three types of bridges, a long span bridge, a three-piece bridge, and a single crown, were made from each of the colored zirconia blanks obtained in Examples 1 to 7, and fitted to a dental arch model to confirm compatibility. The compatibility criteria are as follows. The results are shown in Table 1. <Evaluation criteria for the degree of deformation due to firing> 5: Preferred for long span bridge use 4: Preferred for use with 3-prong bridges 3: Preferred for single crown use 2: Low compatibility 1: Difficult to use clinically

[0059] When the degree of deformation due to firing was confirmed, it was confirmed that the sample evaluated in Example 1 was suitable for use as a long span bridge, the samples evaluated in Examples 2 and 7 were suitable for use as a three-tooth bridge, and the samples evaluated in Examples 3 and 6 were suitable for use as a single crown. On the other hand, the sample evaluated in Example 4 had low compatibility. "Low compatibility" means that the obtained machined body (dental prosthesis) can be used after fitting adjustment and occlusion adjustment, but it takes time to make the fitting adjustment and occlusion adjustment when wearing it, which places a burden on the dentist at the dental clinic, and when the adjustment is made at the dental clinic, it also places a burden on the patient for a long time (such as sitting on the examination table for a long time), so it is difficult to recommend. The sample evaluated in Example 5 was difficult to use clinically. "Difficult to use clinically" means that the obtained machined body (dental prosthesis) is so loose when wearing it in the oral cavity that it is judged to be unusable even if fitting adjustment and occlusion adjustment are made.

[0060] [Table 1]

[0061] As described above, it was confirmed that the greater the color difference of the colored zirconia blank (the maximum value of the color difference between any two layers), the greater the degree of deformation due to firing, and the lower the suitability for a dental arch model. In other words, it is suggested that the evaluation method of the present invention based on the color difference makes it possible to select a more suitable application from many types of disks without cutting and firing the zirconia calcined body, and to efficiently manufacture dental prostheses. [Industrial Applicability]

[0062] The evaluation method of the present invention can be used for zirconia blanks having a multilayer structure.

Claims

1. A coloring step of coloring all layers of the zirconia calcined body having at least two layers with a coloring agent by impregnating the surface of the zirconia calcined body with a coloring solution; and a step of measuring the L*a*b* value of each layer in the L*a*b* color system for all layers of the zirconia calcined body colored in the coloring step, calculating the color difference ΔE*ab between each layer by the following formula (1), and predicting and evaluating the degree of deformation of the zirconia calcined body during firing based on the maximum value of the color difference ΔE*ab. An evaluation method for predicting and evaluating deformation due to firing of a zirconia calcined body before obtaining the zirconia sintered body. ΔE*ab={(ΔL*) 2 + (Δa*) 2 + (Δb*) 2} 1 / 2 (1)

2. The evaluation method according to claim 1 , wherein the zirconia calcined body is a zirconia blank.

3. The evaluation method according to claim 1 , wherein the zirconia calcined body is a processed body having a shape of a dental prosthesis.

4. The evaluation method according to any one of claims 1 to 3, wherein the coloring step of coloring the zirconia calcined body with a colorant is carried out by immersing the calcined body in the coloring solution or applying the coloring solution.

5. A step of predicting and evaluating deformation due to sintering of a zirconia blank before obtaining a zirconia sintered body by the evaluation method according to claim 2; and processing the zirconia blank according to the degree of deformation to produce a dental prosthesis. A method for manufacturing dental prostheses.

6. A step of predicting and evaluating deformation due to firing of a zirconia calcined body or a processed body thereof before obtaining a zirconia sintered body by the evaluation method according to any one of claims 1 to 4; The zirconia calcined body or its processed body is fired. A method for manufacturing dental prostheses.

Citation Information

Patent Citations

  • Multilayered zirconia, each layer having different content of yttria

    JP2019163246A

  • Zirconia calcinated body and zirconia sintered body, and laminate

    JP2020075858A

  • Dental ceramic material

    JP2020109069A

  • Method for estimating specific surface area of powder, estimation device and program

    JP2020165801A

  • Method of Coloring Multi-Layered Pre-Sintered Dental Restoration

    US20180263740A1